Determinant of Milk Production in Northwestern and Western Zones of Tigray, Ethiopia - Desale Gebretsadik; Abrehaley Tikue; Teklemariam Abadi; Danial Desta; Gebrekiros Maru (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
This study identifies the main determinants of milk production in Northwestern and Western zone of Tigray region using both secondary and primary data sources collected through survey, KII and FGD. The cross-sectional data type has collected during 2018 from 309 smallholder dairy cattle keeper farmers randomly selected following multistage sampling technique. It has so found that the average milk yield obtained per cow per day was 2.53 and 3.3 3Lt; milked for the average number of 27 and 26 days per month for the average number of 6.3 and 6.4 months. So that the total produced amount of milk was 1166.25Lt and 2291.29Lt per household, respectively for Tahtay adiyabo and Kafta humera districts. Applying multiple linear regression analysis, the major determinants of milk yield in Tahtay adiyabo district are; number of months that collected/concentrated feed has provided for dairy cows, education level of the household head, place where milk has sold and loan obtained especially for dairy production. These variables have positive and significant relationship. While, variables such as distance of cattle farm from local market, total family size and marital status of the household head has significant and negative relationship. Similarly, in Kafta humera district the determinant factors are; number of months that collected feed provided, occurrence of cattle pests and diseases, education level of household head and experience in cattle rearing has significant and positive relationship. While, variables such as sex of the household head, distance of water source that dairy cattle travel and extension contact in livestock production has significant and negative relationship with milk yield obtained. Based on these findings this study recommends that, capacity building; organizing smallholder farmers by nearby and establish functional milk and its product supplying cooperatives. It is also important that dairy cows should provide concentrated and collected feed; introduction of improved forages with intensive protection from cattle diseases and pests as well as improving access to drinking water source in nearby are important.